Developing best environmental practice for polymetallic nodule mining - a review of scientific recommendations - Christiansen, Sabine; Bräger, Stefan (Frontiers in Marine Science, 2023)
Best environmental practice (BEP) is a key component of an ecosystem approach to management and is typically a product of practical experience in established industries. For an emerging activity such as deep seabed mining, no such experience will exist at the time of deciding on the permissibility of the first industrial mines. Therefore, experience from deep ocean scientific experiments and research are important to develop a preliminary understanding of BEP for deep seabed mining. This paper offers a detailed review of the scientific literature from which it identifies elements of preliminary BEP for nodule mining. The paper describes the currently envisaged mining process for manganese nodules and its expected effects on the environment and extracts specific recommendations on how to minimise environmental impacts from mining in different layers of the ocean (benthic, benthopelagic, pelagic, and surface waters) as well as from noise and light impacts. In doing so, the paper aims to inform the Mining Code being developed by the International Seabed Authority (ISA). The ISA is the intergovernmental institution mandated to organise and control seabed mining on the international seabed. The ISA is obligated to ensure effective protection of the marine environment from harm likely to arise from mining, with BEP being a core tool to achieve that. This paper provides suggestions for a future ISA Standard on BEP.